The “Great Debate” at Melanoma Bridge 2022, Naples, December 1st–3rd, 2022 - Paolo A. Ascierto; Christian Blank; Alexander M. Eggermont; Claus Garbe; Jeffrey E. Gershenwald; Omid Hamid; Axel Hauschild; Jason J. Luke; Janice M. Mehnert; Jeffrey A. Sosman; Hussein A. Tawbi; Mario Mandalà; et al. (Journal of Translational Medicine, 2023)
Abstract The Great Debate session at the 2022 Melanoma Bridge congress (December 1–3) featured counterpoint views from leading experts on five contemporary topics of debate in the management of melanoma. The debates considered the choice of anti-lymphocyte-activation gene (LAG)-3 therapy or ipilimumab in combination with anti-programmed death (PD)-1 therapy, whether anti-PD-1 monotherapy is still acceptable as a comparator arm in clinical trials, whether adjuvant treatment of melanoma is still a useful treatment option, the role of adjuvant therapy in stage II melanoma, what role surgery will continue to have in the treatment of melanoma. As is customary in the Melanoma Bridge Great Debates, the speakers are invited by the meeting Chairs to express one side of the assigned debate and the opinions given may not fully reflect personal views. Audiences voted in favour of either side of the argument both before and after each debate.